The Impact of COVID-19 on Islamic Rural Banks’ Profitability and Capital Adequacy Ratio - Khaerul Umami; Puji Solikhah; Efi Syarifudin; Dede Sudirja; Setiyawan Gunardi (Mutanaqishah: Journal of Islamic Banking, 2025)
Purpose – This study aims to analyze the impact of the COVID-19 pandemic on the financial performance of Islamic Rural Banks (IRB) in the Banten region, focusing on profitability and capital adequacy ratios as indicators of financial soundness. Methodology – The research employs a quantitative approach, utilizing descriptive and comparative methods. Data from eight IRB institutions in Banten were collected and assessed using the Financial Services Authority Regulation (POJK) No. 3 of 2022 to evaluate the soundness of the IRB. The Paired Sample T-Test was used to analyze four key financial ratios: Return on Assets (ROA), Operating Expenses to Operating Income (BOPO), Capital Adequacy Ratio (KPMM), and Core Capital to Non-Performing Productive Assets (MIAPB). Findings – After the pandemic, profitability declined significantly, with average ratings falling from 3 (moderately adequate) to 4 (less adequate). This decline was evident in lower ROA and higher BOPO, reflecting reduced operational efficiency and profit margins. Capital adequacy remained stable at 2 (adequate), unaffected by the pandemic. Implications – These findings demonstrate the vulnerability of Islamic microfinance institutions to profitability during crises, while also highlighting their resilient capital structures. Policymakers and banking practitioners can utilize these insights to develop adaptive strategies that enhance operational efficiency and crisis preparedness in Islamic banking. Originality – This study contributes to the limited empirical research on the post-COVID-19 financial health of IRB in Indonesia, particularly in Banten province. It uniquely applies the updated POJK No. 3/2022 and integrates profitability and capital indicators to evaluate the resilience of Islamic rural banks during a global health crisis.